Investigation Of Musculoskeletal Disorders Among Workers In Food Services (Cafeteria) - Kamat, Seri Rahayu; Nordin, Eezsafauzia Azalin; Husain, Kalthom; Syed Ali, Sharifah Aznee (Human Factors And Ergonomics Society Malaysia (HFEM), 2017)

(untitled)
In commercial food services, the workers are exposed to various risks factors such as awkward postures, repetition of the body movement, heat stress, prolonged standing, poor lighting and vigorous vibration that are led to work-related musculoskeletal disorders (WMSDs). The aim of this paper is to investigate the impact of ergonomics risk factors on worker’s postures while performing kitchen daily activities. The method adopts qualitative method on the physical experience discomfort through the interview session, workplace observation and questionnaires survey to all workers. This project started with determining the physical discomfort which influenced worker working posture while performing daily kitchen activities. The result concluded that most of the respondents faced severe pain in their upper back and lower back. This is due to kitchen daily activities usually involving repetitive and forceful task where workers are required to perform the task in prolonged working hours hence lead to the development of muscle fatigue. The effect of risk factors on the working posture of UTeM’s Cafeteria workers while performing daily kitchen activities is determined by analysing the worker posture using RULA Analysis. Based on the result obtained, the total score for all working posture for current cooking area involving male and female workers are high and required immediate improvement.